Identifying the language skill of consecutive interpreters. Towards the development of recommendations on language choices in interpreters’ notes - SASAKI, ANNA (International Journal of Language, Translation and Intercultural Communication, 2018)
This article reports on a small-scale empirical study on note-taking in consecutive interpretation. Present-day interpretation labor market has faced a number of changes, as nowadays interpreters challenge themselves to work with different language combinations. A sufficient level of an in-demand language skill is now critical for employability of young trainees in the labor market. The present research illustrates the way interpreter trainees with different language skill sets carry out similar tasks in different interpretation settings. For primary research data, the study uses results of a background survey, complete with audio recordings of the performance and the notes produced by eight subjects while interpreting an English source text consecutively into Japanese. The aim of the study is to explore the differences in consecutive interpretation of interpreters in classical settings (L2 to L1) and in emerging new trends in the labor market (L2 to L3). The article argues that the language skill required for each trend in the interpretation labor market is defined by the specific interpretation settings.